2016
DOI: 10.1002/wcs.1393
|View full text |Cite
|
Sign up to set email alerts
|

Language learning, socioeconomic status, and child‐directed speech

Abstract: Young children’s language experiences and language outcomes are highly variable. Research in recent decades has focused on understanding the extent to which family socioeconomic status (SES) relates to parents’ language input to their children and, subsequently, children’s language learning. Here, we first review research demonstrating differences in the quantity and quality of language that children hear across low-, mid-, and high-SES groups, but also—and perhaps more importantly—research showing that differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
130
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(154 citation statements)
references
References 98 publications
8
130
1
3
Order By: Relevance
“…There are different factors, such as genetic background, sex, intrauterine growth restriction, nutrition, maternal education, and socioeconomic status, among others, that have an important role during brain development [39]. Others researchers have reported that children born in families with lower socioeconomic status showed slower language development [40,41]. Furthermore, the results of the current study are in agreement with other study reporting that the beneficial effects of breastfeeding on language skills in children at five years old were reduced when social and parental factors were taken into account [42].…”
Section: Discussionmentioning
confidence: 99%
“…There are different factors, such as genetic background, sex, intrauterine growth restriction, nutrition, maternal education, and socioeconomic status, among others, that have an important role during brain development [39]. Others researchers have reported that children born in families with lower socioeconomic status showed slower language development [40,41]. Furthermore, the results of the current study are in agreement with other study reporting that the beneficial effects of breastfeeding on language skills in children at five years old were reduced when social and parental factors were taken into account [42].…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneous factor has been discussed repeatedly in the literature on language acquisition, saliently in Hart and Risley (), who focused on English‐learning American infants, but also in much other work, for instance, that documenting variation among infants growing up in Guatemalan rural households (Klein et al., ). There are numerous pathways through which SES could potentially account for structured variance in input quantity (see Pace, Luo, Hirsh‐Pasek, & Golinkoff, ; Schwab & Lew‐Williams, for recent reviews). To mention just three, all else equal: (a) families with lower SES may experience harsher living conditions, with negative consequences for their emotional well‐being leading to poorer infant–caretaker attachment (e.g., Hackman, Farah, & Meaney, , p. 653 ff.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic disparities in children's language and literacy skills are well‐documented, persistent, emerge early and widen over time (Pace, Luo, Hirsh‐Pasek, & Golinkoff, ; Schwab & Lew‐Williams, ). Socioeconomic factors, such as family income and parental education, are distal factors that likely exert their effects on development via proximal environmental factors, which in turn impact the brain in ways that explain observable cognitive performance.…”
Section: Theoretical Mechanisms Underlying Socioeconomic Disparities mentioning
confidence: 99%